CP-069 Quality of antibiotic treatment in preterm neonates: a ready-to-use formulation of gentamicin sulphate. (24th March 2015) - De Meo, MS; Polidori, C; Pompilio, A; Carnielli, V; Savini, S; Ciuccarelli, F; Andresciani, E; Garzone, A; Carloni, L; Moretti, V
Abstract : Background: Intravenous (IV) drug treatment of preterm neonates is affected by: clinical status (i.e. sepsis/infections, immature physiology, pharmacokinetic/pharmacodynamic variation), shortage of ready-to-use formulations, small doses of drug required and the dangers of the IV route. Purpose: To identify the most prescribed IV antibiotics so that ready-to-use formulations can be prepared with standard concentrations (SCs) of drug avoiding handling (reconstitution/dilution) in the ward. Material and methods: The Hospital Pharmacy, Neonatology and Hygiene Department of "Azienda Ospedali Riuniti-Ancona" conducted this multiphase study. Phase I: a review of IV antibiotics prescribed to preterm (24 +0 –31 +6 weeks) Neonatology inpatients from 2004–2013. Phase II: study of pharmaceutical quality and stability of SC (2 mg/ml) gentamicin sulphate (the gold standard in sepsis/infections). Aqueous solutions were prepared by pharmacists in two different ways: with and without filtration. Both batches were stored in polyethylene syringes for 90 days at 2–8°C and 25°C and were examined for: endotoxin absence with the LAL test (Limulus amoebocyte lysate, Endosafe Portable Test System) in accordance with the Italian Pharmacopoeia 12th edition (kinetic-chromogenic technique); sterility test (BacT/ALERT FA, six days of incubation at 36°C) for aerobic bacteria/fungi; quantification with HPLC-MS/MS technique of gentamicin components (C1, C2, C1a ) at 0–3–7–14–21–28–60–90 days. Limits of detection (LOD) and quantitation (LOQ) were 0.25 ng. The SC was derived from the usual dose (2.5 mg/kg/12 h) for a 1, 000 g patient. Results: Phase I studies found: 1, 011 preterm inpatients (521 males, 420 females), 222 cases of sepsis (52 early, 170 late) and 102 infections. Gentamicin was the most used antibiotic with 1, 126 doses for 88 patients per year. Phase II studies certified: sterility (no microbiological growth), absence of endotoxins and stability of GS 2 mg/ml stored 90 days at 2–8°C and 25°C. No significant changes in concentration of gentamicin components: P not significant, t-test >0.05. Conclusion: After this "pilot study" the next target could be to provide standard concentration unit dose treatments direct from the pharmacy to paediatric patients. References and/or Acknowledgements: No conflict of interest.